PENSION REFORM AND ITS IMPACTS ON BENEFICIARIES' INCOME (Editora Impacto Científico, 2025)
The present study investigated the impacts of the 2019 Social Security Reform, enacted by Constitutional Amendment No. 103/2019, on the income of beneficiaries and its relationship with social inequalities in Brazil. The research, based on bibliographic and qualitative methodology, employed a deductive approach, drawing upon primary sources (the 1988 Federal Constitution, Constitutional Amendment No. 103, and Law No. 8,213 of July 24, 1991) and secondary sources (Manual of Social Security Law, Das Kapital, Social Security Law Course, among others) for analysis. The work was divided into two parts: the first focusing on Social Security as a fundamental right and detailing the 2019 reform; and the second correlating the reform with social inequality from the Marxist perspective of wage labor. The aim was to understand how modifications in the social security system can influence equity structures in the country, evaluating whether they align with the ideals of justice and equality of the 1988 Federal Constitution.